Adaptation Options for Rice-Based Cropping Systems in Climate Risk-Prone Provinces in the Mekong River Delta: An Assessment Report - Bong, Bui Ba; Nguyen Hong Son; Bo, Nguyen Van; Tung, Le Thanh; Tu, Trinh Quang; Toan, To Quang; Sebastian, Leocadio S.; Yen, Bui Tan; Trung, Nguyen Duc; Labios, Romeo (2018)
This report highlights the results of consultation meetings and field visits organized by the Department of Crop Production and the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia in association with the five offices of the Department of Agriculture and Rural Development in the Mekong River Delta provinces of An Giang, Can Tho, Dong Thap, Long An, and Tra Vinh. This assessment report also looks at various issues that affect the agricultural transformation of the region such as failure to recognize risks brought about by climate change, unpredictable prices of agricultural products in the local and world market, lack of linkages between farmers and potential markets, lack of knowledge and skills in growing new crops, and spontaneous breaching of provincial government plans in changing cropping systems, and more investments in modernizing agricultural infrastructure, among others. The report draws upon the critical importance of the master plan mentioned earlier in rice restructuring within the context of the whole Mekong Delta to guide and shape the actions of the visited provinces. Climate-related risks maps and adaptation plans (CS MAP), which is applied in the five Mekong Delta Region provinces, are found to be valuable in complementing the planting calendar of rice seasons.